Percepción de bienestar a partir del uso de métodos alternativos y convencionales para el tratamiento de los trastornos de ansiedad y depresión (2023)
The present research work aims to understand the perception of wellbeing constructed by some of the members of ASODEP, when using alternative and conventional methods of clinical intervention for the treatment of anxiety and depression disorders; its theoretical and methodological approach belongs to basic exploratory research with a narrative design that allows the collection and analysis of qualitative data from the historical-hermeneutic approach using the computer program Atlas.Ti